Translation, Cross-cultural Adaptation and Psychometric Properties of the Parental Feeding Style Questionnaire into Brazilian Portuguese Language - de Sousa, Karina Guedes; Gavião, Maria Beatriz Duarte; Ultremari, Natalia de Freitas; Júnior, Samuel de Carvalho Chaves; Barbosa, Taís de Souza [UNESP] (FapUNIFESP (SciELO), 2023)
Objective: To translate, cross-culturally adapt and test the psychometric properties of the Parental Feeding Style Questionnaire (PFSQ) to Brazilian Portuguese language. Material and Methods: Three stages were carried out: 1st, the 27-item of PFSQ was translated, back-translated, reviewed by a Committee of Experts and pre-tested (n=60), obtaining the cross-culturally adapted version. 2nd, the final version was self-applied by 42 mothers for internal consistency (Cronbach’s Alpha). After 2-weeks, 19 mothers answered the PFSQ again for reproducibility (Intraclass Correlation Coefficient, ICC). 3rd, 204 mothers of children aged 4-5 years answered the PFSQ for translation validation [convergent validity and exploratory factor analysis (EFA)]. Results: For subscales, Cronbach’s alpha ranged from 0.65 to 0.82; the overall reliability was 0.69, indicating substantial internal consistency. The ICC for overall PFSQ was 0.78 and for domains 0.56-0.89, indicating moderate to excellent reproducibility. ‘Control over eating’ correlated positively with ‘prompting/encouragement to eat’ and negatively with ‘instrumental feeding’; ‘prompting/encouragement to eat’ correlated positively with ‘emotional feeding’. By EFA, PFSQ items were loaded on four factors. ‘Control over eating’ and ‘prompting/encouragement to eat’ settled into two factors, whereas the ‘emotional’ and ‘instrumental feeding’ domains into one factor each. Conclusion: Despite the different factors found by AFE related to the original PFSQ, the reliability was satisfactory, making the Brazilian Portuguese version of the PFSQ adequate to assess parental feeding style.
Keywords: Child; Feeding Behavior; Mothers; Surveys and Questionnaires; Translation